Frequency-division multiplexer and demultiplexer for terahertz wireless links - Jianjun Ma (Nature Portfolio, 2017)
There is growing interest in the development of components to facilitate wireless communications in the terahertz but the characterization of these systems involve an unmodulated input. Here the authors demonstrate multiplexing and demultiplexing of data streams in the terahertz range using a real data link.